Muscotoxins: novel cytotoxic undecapeptides with unique structural elements and mechanism of action, isolated from soil cyanobacterium Nostoc muscorum. - Tomek, Petr (Jihočeská univerzita, 2010)
This project was focused on development of extraction and purification protocol for novel cytotoxic compound isolated from soil cyanobacterium Nostoc muscorum which would allow to determine its molecular structure via NMR (nuclear magnetic resonance) and MS (mass spectrometry) techniques. Purified cytotoxin was subjected to several biochemical and microscopical experiments in order to assess its toxicological parameters, determine the mechanism of action and evaluate potential application in biotechnology or pharmacy.
Muscotoxins: novel cytotoxic undecapeptides with unique structural elements and mechanism of action, isolated from soil cyanobacterium Nostoc muscorum
Keywords: cyanobacteria; Nostoc; cytotoxicity; secondary metabolites; chromatography; spectrometry; cytotoxin; muscotoxin; cell